Reading Strategies in Narrative Text Comprehension: A Case Study of Indonesian EFL Junior High School Students - Fitri; Bimas Reskiawan; Susi Astiantih; Roslina (Faculty of Education and Teacher Training of UIN Palopo, 2026)
Low reading interest and comprehension difficulties among EFL junior high school students, particularly in understanding narrative texts, remain significant challenges in Indonesian education, especially in rural settings. This mixed-methods research investigated the reading strategies used by third-grade junior high school students in comprehending narrative texts and how they use those strategies in reading class. A qualitative case study design was employed, supported by quantitative data from a questionnaire. The subjects were 27 third-grade students at a junior high school in Kolaka Regency, Southeast Sulawesi. Data were collected through classroom observations using field notes and a questionnaire based on (Banditvilai, 2020) framework of four reading strategies: skimming, scanning, making predictions, and questioning. Thematic analysis was applied to qualitative data, while descriptive statistics (percentages) were calculated for quantitative data. The findings revealed that students employed all four strategies with distinct patterns. Skimming and scanning functioned as efficiency-oriented strategies: 74.1% of students sometimes skipped small details during reading. Prediction and questioning functioned as depth-oriented strategies: 55.6% often compared predictions with actual information. The integration of questionnaire and observation data through methodological triangulation indicates that students actively combine multiple metacognitive strategies. However, the gap between